تحليل محتوى كتاب دروس اللغة العربية الجزء الأول للإمام الزركشى والإمام الشبانى من التراكيب وأثرها في فهم النصوص الإسلامية - Hurriyatus Sa'adiyah; Indra Saputra (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
Textbooks are one of the things that are very important in the learning process. Therefore, teachers and educators must prepare it very well so that the desired learning objectives can be achieved. The use of textbooks must adapt to the methods, objectives, and learning media. The purpose of this study was to analyze the contents of the book Durus al Lughah al Arabiyah Juz I by Imam Zarkasyi and Imam Syubani from one aspect of the language, namely tarkib (sentence structure). As is known, mastery of tarkib is very important in understanding Islamic teachings, because the source, the Quran, Hadith, and the books of Islamic scholars, use Arabic. Without good mastery, texts that speak Arabic can be wrong and difficult to understand. The method used in this study is the method of content analysis by analyzing this book Durus al Lughah al Arabiyah Juz I. The results of the research are that the author did not find special material on tarkib learning in this book. In accordance with the purpose of writing, namely the application of speech, the tarkib is directly learned in a sentence. This sentence is given from a simple form and gradually changes to a more complex sentence accompanied by exercises on each material. Among the forms of tarkib training are question and answer, word changes, sentence improvement, etc.